Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai di Kantor Kecamatan Solokan Jeruk - Rosdiana, Yana; Suryanto, Suryanto; Alhadihaq, Muhammad Yusuf (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Local government is a government that has its own autonomy. The autonomous government has the authority to regulate and manage the needs of its region. The foundation of authority that forms the basis of regional autonomy is based on law number 6 of 2014 concerning Regional or Village Government. Regional or village government policies aim to provide rights services to the community in a more managed manner. Employee performance is one manifestation of the existence of local government which is considered good or bad according to the response of society in general. The achievement of a good employee performance is influenced by internal forms in a government, one of which is organizational culture in government. Therefore, organizational culture in government will affect the performance of employees or apparatus provided to meet the needs of society. The research design was carried out by using quantitative research methods based on survey results presented in statistical form. The research subjects consisted of 40 respondents with organizational culture variables and employee performance variables in the Solokan Jeruk District office. The results of the data obtained indicate that organizational culture has a significant influence on employee performance.